2018
DOI: 10.1002/bmc.4254
|View full text |Cite
|
Sign up to set email alerts
|

Fast and sensitive HPLC/UV method for cefazolin quantification in plasma and subcutaneous tissue microdialysate of humans and rodents applied to pharmacokinetic studies in obese individuals

Abstract: Antimicrobial prophylactic dosing of morbidly obese patients may differ from normal weighted individuals owing to alterations in drug tissue distribution. Drug subcutaneous tissue distribution can be investigated by microdialysis patients and animals. The need for cefazolin prophylactic dose adjustment in obese patients remains under discussion. The paper describes the validation of an HPLC-UV method for cefazolin quantification in plasma and microdialysate samples from clinical and pre-clinical studies. A C c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The influence of several other factors has been studied as well, but the influence on protein binding was not present or not relevant. For cefazolin several studies investigated whether there was a differences between (morbidly) obese and non—obese patients ( Van Kralingen et al, 2011 ; Hites et al, 2016 ; Palma et al, 2018 ; Dorn et al, 2019 ). It was concluded that obesity did not influence protein binding.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of several other factors has been studied as well, but the influence on protein binding was not present or not relevant. For cefazolin several studies investigated whether there was a differences between (morbidly) obese and non—obese patients ( Van Kralingen et al, 2011 ; Hites et al, 2016 ; Palma et al, 2018 ; Dorn et al, 2019 ). It was concluded that obesity did not influence protein binding.…”
Section: Resultsmentioning
confidence: 99%
“…The application of the HPLC methods for the measurement of antibiotic concentrations in biological samples in clinical microbiology laboratories have been reported by White (54). Developed chromatographic methods for the determination of antibiotics in biological materials are characterized by different types of detection, such as high-performance liquid chromatography (HPLC) methods with an electrochemical detection (ECD) (55), fluorescence detection (FLD) (56)(57)(58)(59)(60), ultraviolet (UV) detection (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77) and mass spectrometry (MS) detection (78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97).…”
Section: Methods Of Quantifying Antibiotics In Biological Samplesmentioning
confidence: 99%